Effect of Sending Educational Video Clips via Smartphone Mobile Messenger on Bowel Preparation before Colonoscopy - Sung Chan Jeon; Jae Hyun Kim; Sun Jung Kim; Hye Jung Kwon; Youn Jung Choi; Kyoungwon Jung; Sung Eun Kim; Won Moon; Moo In Park; Seun Ja Park (Clinical Endoscopy, 2019)
Background/Aim We aimed to evaluate the efficacy of sending educational video clips via smartphone mobile messenger (SMM) on enhancing bowel preparation before colonoscopy. Methods This was a prospective, endoscopist-blinded, randomized controlled study. Patients in the SMM group received two video clips sent via SMM that explained the diet and regimen for bowel preparation, whereas those in the control group did not receive any video clips. We compared the quality of bowel preparation between the two groups, which was assessed by an endoscopist using the Ottawa scale. Results Between August and November 2014, 140 patients in the SMM group and 141 patients in the control group underwent colonoscopic examination. T﻿he total Ottawa score of the SMM group was significantly lower than that of the control group (5.47±1.74 vs. 5.97±1.78, p=0.018). These results were particularly prominent in the younger age group; the total Ottawa score of patents in the SMM group aged <40 years was significantly lower than that of patients in the control group aged <40 years (5.10±1.55 vs. 6.22±2.33, p=0.034). Conclusions We demonstrated that sending educational video clips via SMM could result in better bowel preparation, especially in the younger age group.